Cease agricultural activity forever? Underestimating the importance of symbolic capital. (April 2016) - Conway, Shane Francis; McDonagh, John; Farrell, Maura; Kinsella, Anne
Abstract: Similar to what is occurring on a global scale, Irish agriculture is populated by an older generation of farmers. Consequently, intergenerational family farm transfer is increasingly viewed as crucial to the survival, continuity and future sustainability of the family farm and agricultural sector. A review of existing research highlights how financial incentives that encourage succession and retirement from farming have stimulated little change in the behavioural intentions and attitudes amongst elderly farmers. Drawing on two previously disparate literature (transferring the family firm and transferring the family farm) and applying Pierre Bourdieu's concept of symbolic capital as a theoretical framework, this paper sets aside financial enticements and presents an insightful, nuanced analysis of the human factors that influence the process of transferring the family farm from the perspective of the senior generation. This research employs a multi-method triangulation design, consisting of self-administered questionnaires in conjunction with complimentary Problem-Centred Interviews, to acquire data on the complex psychodynamic and sociodynamic emotions involved in the process. The prominent themes to emerge from the empirical data are farmer's concerns regarding potential loss of identity, status and control upon transferring management and ownership of the family farm and retiring. Many older farmers appear to prioritise the building and maintenance of their personal accumulation of symbolic capital rather than ceasing agricultural activity. The paper concludes by suggesting that future policies and programmes encouraging family farm transfer must take into account the pervasiveness of symbolic capital and work within this structure to develop effective strategies that addresses the emotional well-being of elderly farmers. Highlights: There are concerns about the sustainability of an aging farming population. Financial incentives encouraging family farm transfer fail to deal with the emotional issues facing ageing farmers. Transferring management and ownership of the farm and retiring returns little symbolic capital to older farmers. Farmers opt to maintain the facade of normal day to day farming activity and behaviour in old age. Future policies must take into account the emotional well-being of farmers and work within this structure to effect change.